Navigating Islamic equity crowdfunding: a case study of Ata Plus in Malaysia - Ramli, Habibah Solehah; Abdullah, Md. Faruk; Alam, Md. Kausar (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
The objective of this study was to investigate the operation of Ata Plus, the primary equity-based Islamic crowdfunding platform in Malaysia. The data was collected through document analysis and by conducting interviews with top-level executives at Ata Plus. This study revealed that Ata Plus was founded to address the financial concerns of the increasing number of Small to Medium Enterprises (SMEs) in Malaysia. The funding implementation for the enterprises was based on the use of the Mudharabah contract. The crowdfunding operation of Ata Plus was regulated by the Securities Commission Malaysia (SCM), which established criteria for various categories of investors, businesses, and the platform. Ata Plus performed a thorough assessment of the company’s creditworthiness through a comprehensive background analysis. Additionally, it implemented steps to ensure transparency in the project’s operations. It is learned that although Ata Plus’s core business was in line with the Shariah it needs to improve its Shariah governance system through appointing qualified Shariah scholars to conduct Shariah supervisory functions. This research contributes fresh insights by demonstrating the practical implementation of Islamic equitybased crowdfunding, which was previously only discussed in the theoretical literature.